The Spatial Suitable Habitat Model of Acacia decurrens in Mount Merbabu National Park - Yoko Untoro; Agus Hikmat; Lilik Budi Prasetyo (Department of Forest Resources Conservation and Ecotourism - IPB University, 2017)
Green wattle (Acacia decurrens) is an invasive alien species (IAS) found in the Mount Merbabu National Park (TNGMb). This study aim to obtain spatially studies on habitat suitability models of A. decurrens in TNGMb region. In fact, this species became as a high invasive and dominance in the TNGMb and contributes the negative impact to the ecosystem. In addition, the result of this study should be useful for controling activities of A. decurrens. Predictor variables in this research were (altitude, slope, rainfall, air temperature, distance from river, NDVI, NDMI, distance from hiking trail, and distance from burnt area). The survey was conducted with random sampling of presence or absence of A. decurrens by marking the coordinate point of location using GPS. Data analysis in this research was used binary logistic regression enter method. Binary logistic regression involves the data acquisition of the presence and absence of A. decurrens as the y variable, while the predictor variable map as the variable x. The type of spatial distribution of A. decurrens in the TNGMb was identified as clumped. The Nagelkerke R2 values obtained in the model was 39,2%, while 60,8% was explained by other variables were not used in the model. The results of the logistic regression model showed a high percentage of suitability of 64,29%, a medium suitability of 28,57%, and a low suitability of 7.14% then the Implications for controlling activities of A. decurrens in TNGMb could be prioritized in high suitability habitat. Keywords: Acacia decurrens, green wattle, invasive, spatial suitable habitat